Evaluation of Communicable Diseases Control Surveillance System Quality at Primary Health Care Centers in Kirkuk Governorate - Mohammed F. Khalifa (Journal of Global Pharma Technology, 2016)
Objective: To evaluate the communicable diseases control surveillance system structure, process, and outcome and it is quality throughout indicate level of usefulness of surveillance system characteristics of completeness, timeliness, usefulness, sensitivity, positive predictive value (PPV), specificity, representativeness, simplicity, flexibility, acceptability, and reliability. Methodology: descriptive evaluation study is conducted on primary health care centers in Kirkuk Governorate from October 14th 2017 to May 1st 2018.A probability sample of (30) unit which is selected from communicable disease of surveillance system units. Data were collected throughout the utilization of the adopted questionnaire and interview technique. Questionnaire has been selected for primary health care centers consists of (80) items. Results: The study results indicate that communicable disease surveillance system structure is adequate in primary health care centers and primary health care sectors. While, the system experienced inadequate surveillance system process in primary health care centers and primary health care sectors. Recommendations: The study recommends that further research studies can be conducted on large-scale sample size and local, as well as national levels studies can be steered. Sufficient and efficient staff can be appointed to take the accountability for employing the communicable disease surveillance system in order to achieve maximum benefits from the system.Keywords: Evaluation, Communicable Diseases Control Surveillance System, Primary Health Care Centers.